Socioeconomic and Environmental Implications of Agricultural Residue Burning A Case Study of Punjab, India - Kumar, Parmod; Kumar, Surender; Joshi, Laxmi; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2015)
This book discusses the important issue of the socioeconomic and environmental impacts of agricultural residue burning, common in agricultural practices in many parts of the world. In particular, it focuses on the pollution caused by rice residue burning using primary survey data from Punjab, India. It discusses emerging solutions to agricultural waste burning that are cost-effective in terms of both money and time. The burning of agricultural residue causes severe pollution in land, water and air and contributes to increased ozone levels and climate change in the long term. However, appropriate assessments have not been undertaken so far to demonstrate the relevant impact of agriculture-based pollution, especially residue burning. This book addresses this gap in the literature. Punjab has been used as a case study as it is the chief granary of India, contributing to 27.2 percent of the Indian national produce of rice and 43.8 percent of wheat. It is presumed that the findings fromthis state will be useful not only for other agricultural areas in India, but across the world. This book, therefore, sensitizes policy makers, researchers and students about the impacts of air pollution caused by agricultural residue burning---a subject not much dealt in the literature---and provides a way forward.
Chapter 1: Problem of Residue Management due to Rice Wheat Crop Rotation in Punjab -- Chapter 2: The Extent and Management of Crop Stubble -- Chapter 3: Valuation of the Health Impact -- Chapter 4: Alternative Uses of Crop Stubble -- Chapter 5: Environment Legislation in India as a Whole and in the State of Punjab -- Chapter 6: Policies for Restricting the Agriculture Residue Burning in Punjab -- Chapter 7: Concluding Remarks and Policy Implications -- References -- Annexure.
Keywords: Economic sociology; Environmental economics; Biotic communities; Population biology; Economic Sociology; Environmental Economics; Community and Population Ecology